Analytical Method Development for Simultaneous Estimation of Cobicistat and Darunavir by RP-HPLC Method - A. Sindhuja (Journal of Global Pharma Technology, 2018)
A new method was established for simultaneous estimation of Cobicistat and Darunavir by RP-HPLC method.  The chromatographic conditions were successfully developed for the separation of Cobicistat and Darunavir by using Xterra C18 5µm (4.6*250mm) column, flow rate was 1ml/min, mobile phase ratio was Phosphate buffer (0.05M) pH 4.6: ACN   (30:70%v/v)   (pH was adjusted with orthophosphoric acid), detection wave length was 255nm. Five trails have been done with various composition of mobile phase. Among them the mobile phase composition Acetonitrile and phosphate buffer in the ratio of 70:30 (trail no 5), using C18 column as stationary phase and detection at 255nm has produced a well resoluted peak. The no of theoretical plates was 5105, 3788 with a tailing factor of 1.3, 1.4. The peak retention time was 2.399, 3.907 with a peak area of 946124, 11541. The results shown that developed method is rapid, specific for the simultaneous estimation of cobicistat and darunavir in combined dosage form.Keywords: Cobicistat,Darunavir, RP-HPLC, Phosphate buffer, ACN